Efficacy of dietary supplements in clinical recovery after compound fracture of the ankle joint treated with cast - Malatini, Paolo (Progress in Nutrition, 2014)
The sprain of the ankle, pure or associated with distortion results in a period of incapacity or longer and if not properly treated generates significant loss of muscle mass in partion of the quadriceps femoris muscle and the triceps surae, as well as the ability to articulate the ankle. In the delicate phase of clinical recovery post-injury or post-surgery, they play a vital role physiotherapy and proper nutrition, which includes the intensive use of supplements, foods and integrated functional foods. The aim of this observational study was to investigate a sample of 100 patients treated for a compound fracture of the lateral malleolus if nutritional intervention associated with physical therapy and nutritional supplementation can reduce atrophy of the muscles of the lower limb affected by the fracture itself and optimize an adequate muscle recovery during rehabilitation after cast removal. The study duration was 2 months. The patients were divided into two groups: one treated with diet, physiotherapy and nutritional supplementation (Group A) and one with diet and physiotherapy (Group B). The patients were subjected to three visits: beginning the study (T1), 30 days (T2) and 60 days (T3) during which were measured the capacity of the range of movement (ROM) of the ankle and the size of the triceps muscle of the sura. From the data collected is observed a significant difference in the recovery of the size of the triceps surae in group A compared to group B already after 30 days of treatment (T2). In particular it is observed a better maintenance of the tropism in patients of group A, and particularly a recovery of the most important dimensions of the muscle in the same group. Patients in group B instead claimed a major difficulty in functional recovery and especially the trophic muscle was reduced compared with group A; also in the last visit (T3) the volume of the calf is significantly lower than that of both group A compared to the average values of population. Regarding the ROM of the ankle functional recovery was comparable in both group A than in group B at the first visit (T2), while it is observed a statistically significant difference between the two groups in the second visit (T3) where the ROM of the ankle are almost identical to the average population in group A than in group B.